EFEK PEMODERASIAN STATUS KEPEGAWAIAN PADA PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN - Widnyana, I Gusti Ngurah; Sintaasih, Desak Ketut; Riana, I Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016)
The study aims to analyze difference in motivation, organizational commitment, and performance among permanent and outsourced employees, as well as the moderating effect of employment status on the influence of motivation and organizational commitment to employee performance. This research was conducted in PT. Bank Rakyat Indonesia (Persero) Tbk. Kanwil Denpasar, with samples of 67 permanent employees and 67 outsourced employees. Analysis technique using Anova and Moderated Regression. The results show that there is no significant difference between motivation and performance of permanent and outsourced employees, while there are significant difference between two kinds of employee in organizational commitment. Additionally, employee status emerges as moderating variable of influence of motivation and organizational commitment on employee performance. The research can become a reference for the company in improving employee performance in relation with employment status, motivation, and organizational commitment.
Keywords: performance, motivation, organizational commitment, employment status